Kedisiplinan Belajar Siswa Kelas X pada Mata Pelajaran Pendidikan Agama Islam di SMK Ma’arif 1 Kebumen - Taqwawati, Annisa; Khasanah, Nginayatul (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The purpose of the research is: (1) to learn the discipline of the students of class X on the subjects of Islamic Religious Education at SMK Ma’arif 1 Kebumen; The method used in this research is descriptive method. The data collected is observations, interviews and documentation. As for data analysis, the data used is data reduction, data presentation and conclusion drawing. Based on the results of research shows that as far as learning discipline indicators are students apply time discipline, attitude and learning. Where students always come on time, collect tasks in time, apply the 3S (Smile, Sapa and Greetings) and be polite and polite, and most importantly not slipping.